2007
DOI: 10.1111/j.1743-6109.2007.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Female Sexual Dysfunction in Postmenopausal Women by Testosterone Administration: Safety Issues and Controversies

Abstract: Introduction A Food and Drug Administration advisory group has questioned the long-term safety of testosterone administration to postmenopausal women. Although only short-term data exist on safety from the double-blind, placebo-controlled trials, testosterone has been used for more than 50 years. Therefore, some data concerning the long-term safety issues must exist in the literature. Aim To review the published data concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 53 publications
2
42
0
1
Order By: Relevance
“…142 A meta-analysis of studies conducted in 2,795 women receiving background estrogens, alone or in association with progestins, and androgen supplementation within the physiological range suggested that androgens may be safe and not associated with increased cardio vascular risk, although the overall number of cardiovascular events was low. 2 Indeed, reports suggest that androgen supplementation within the physiological range might improve functional capacity in women with heart failure, 143 which might be related to the effect on muscular strength, as the increase in exercise capacity was not coupled with changes in left ventricular function.…”
Section: Cardiovascular Effects In Womenmentioning
confidence: 98%
“…142 A meta-analysis of studies conducted in 2,795 women receiving background estrogens, alone or in association with progestins, and androgen supplementation within the physiological range suggested that androgens may be safe and not associated with increased cardio vascular risk, although the overall number of cardiovascular events was low. 2 Indeed, reports suggest that androgen supplementation within the physiological range might improve functional capacity in women with heart failure, 143 which might be related to the effect on muscular strength, as the increase in exercise capacity was not coupled with changes in left ventricular function.…”
Section: Cardiovascular Effects In Womenmentioning
confidence: 98%
“…Data on the relationship between E2 and CVD risk in men are limited or unreliable despite higher E2 levels measured in men with CAD (18). Few studies have examined endogenous T and CAD in women, with either positive (19) or no (20) correlation between serum levels and CVD reported. In all these studies, steroid levels were measured by immunoassays that provide inaccurate results at low circulating levels (21), which may have contributed to the conflicting findings.…”
mentioning
confidence: 90%
“…The effects of systemic testosterone on female sexual desire are dramatic and have been documented repeatedly, particularly in the last decade. 6 It is difficult to understand how HPRT from transvaginal DHEA could impact the central nervous system when there is little to no change in circulating sex steroids. 1,3 For two decades, these authors have pursued DHEA and refined the concept of HPRT.…”
Section: Editorialmentioning
confidence: 99%